BAKING AND BASEBALL IN INDONESIA: REALIA IN TEACHING AMERICAN CULTURE IN INTENSIVE ENGLISH PROGRAM FOR UNIVERSITY FACULTY/STAFF - Anderson, Roger (International Journal of Education, 2016)
In this reflection, the author reports on his experience teaching English through American culture to Indonesian university educators during three week intensive programs in Indonesia.Â  The author implemented culturally meaningful activities based upon the use of realia, or objects that connect language and on-the-ground reality of native speakers for the foreign language learner.Â  Baseball, baking, the card game Uno, and poetry proved to be successful vehicles for learning.Â  Additionally, emailing between the class and the authorâ€™s contacts in North America provided participants with â€œcase studiesâ€ of real Americans/native speakers of English.Â  Such interactions with actual Americans may provide a useful contrast/compliment to the stereotypical images of Americans disseminated by mass media.Â  Lastly, while the teaching of English and American culture overseas may be controversial to some, this reflection argues that the careful selection of pedagogies can facilitate mutually enriching exchanges.Â  Insights into appropriate realia, subsequent activities, and teaching considerations in Indonesia may be gleaned from this reflection by pedagogues and practitioners alike.